2015
DOI: 10.1631/jzus.b1500006
|View full text |Cite
|
Sign up to set email alerts
|

Decreased PSD95 expression in medial prefrontal cortex (mPFC) was associated with cognitive impairment induced by sevoflurane anesthesia

Abstract: Abstract:Objective: Though sevoflurane has been widely used as an anesthetic in surgery, recent studies have shown that exposure to sevoflurane alone could lead to postoperative cognitive dysfunction (POCD), of which the mechanisms still remain largely unknown. The medial prefrontal cortex (mPFC) is known to be implicated in various cognitive impairments, including working memory and attentional processes. In the present study, we tried to identify dysregulated gene expression in mPFC and investigate the under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…For instance, Zhang et al (8) reported that inhalation of Sevoflurane exposure in postnatal rats induced long-term cognitive impairment through upregulating caspase-3/cleaved-poly (ADP-ribose) polymerase pathway sevoflurane may reduce synaptotagmin-1 protein levels in the hippocampus, which then reduced the efficiency of synaptic transmission, thus resulting in memory impairment in rats. In one of our previous studies, decreased PSD95 expression in the medial prefrontal cortex was also observed in mice with cognitive impairment induced by sevoflurane (9). Furthermore, Xiong et al (10) reported that the CREB signaling pathway was inhibited in aged rats following exposure to sevoflurane.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…For instance, Zhang et al (8) reported that inhalation of Sevoflurane exposure in postnatal rats induced long-term cognitive impairment through upregulating caspase-3/cleaved-poly (ADP-ribose) polymerase pathway sevoflurane may reduce synaptotagmin-1 protein levels in the hippocampus, which then reduced the efficiency of synaptic transmission, thus resulting in memory impairment in rats. In one of our previous studies, decreased PSD95 expression in the medial prefrontal cortex was also observed in mice with cognitive impairment induced by sevoflurane (9). Furthermore, Xiong et al (10) reported that the CREB signaling pathway was inhibited in aged rats following exposure to sevoflurane.…”
Section: Introductionmentioning
confidence: 71%
“…Behavioral experiments. As described in our previous study (9), three tests were conducted in sequence, including the elevated plus-maze (EPM), O-maze and Y-maze. For each behavioral test, the movement tracks of experimental rats were recorded by a video-tracking software (Any-Maze version 5.1; Stoelting Co., Wood Dale, IL, USA) and analyzed by an additional researcher who was blinded to the experimental protocols.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The possible mechanisms of POCD investigated included platelet activation (17), oxidative stress (18), cholinergic function impairment (19,20), impairment of synaptic integrity (2,21), similar mechanisms of Alzheimer's disease (AD) such as beta-amyloid accumulation (22,23) and tau phosphorylation (24), and immune response and inflammation related mechanisms such as the bone marrow-derived macrophages recruitment in hippocampal area (25) and the recent popular surgery-induced neuroinflammation (12,26,27) (Table 2).…”
Section: Mechanismsmentioning
confidence: 99%